IMPACT OF SHEA BUTTER PROCESSING ON HOUSEHOLD BASIC NEEDS IN SELECTED DISTRICTS OF THE NORTHERN REGION OF GHANA - Alhassan, I. (UDS International Journal of Development, 2020)
The researcher conducted a descriptive survey research in three districts of the Northern Region of Ghana to ascertain the impact of shea butter processing on household basic needs in these districts, challenges confronting shea butter processors and as well as examine the policy and regulatory environments of this very important industry on which the livelihoods of many rural women depend. The research revealed that shea butter processing has enhanced the ability of processors to meet their food, clothing, school expenses, health needs as well as social obligations. However, there are challenges such as inadequate capital, low sale of butter, high cost/inadequacy of equipment, laboriousness of butter processing and lack of effective government policy. The study recommends the use of improved technology, linking shea butter processors to reliable funding sources, capacity building for shea butter processors, collaboration among stakeholders in the shea industry, a review of the biological life of the shea tree and the enactment of a policy instrument for the shea industry. Keywords: Shea Butter Processing, Industry, Livelihood, Household, Basic Needs